2017
DOI: 10.1111/1462-2920.13705
|View full text |Cite
|
Sign up to set email alerts
|

Cold adaptation of the Antarctic haloarchaea Halohasta litchfieldiae and Halorubrum lacusprofundi

Abstract: Halohasta litchfieldiae represents ∼ 44% and Halorubrum lacusprofundi ∼ 10% of the hypersaline, perennially cold (≥ -20°C) Deep Lake community in Antarctica. We used proteomics and microscopy to define physiological responses of these haloarchaea to growth at high (30°C) and low (10 and 4°C) temperatures. The proteomic data indicate that both species responded to low temperature by modifying their cell envelope including protein N-glycosylation, maintaining osmotic balance and translation initiation, and modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 121 publications
(197 reference statements)
2
37
0
Order By: Relevance
“…Haloarchaea live and proliferate in extreme environments, characterized by salt concentrations up to saturation, high temperatures (although, some are cold adapted; Dassarma et al, ; Williams et al, ), high solar radiation and high ionic strength (Oren, 2013a; ; ). Under these conditions, oxygen availability is low (Oren 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Haloarchaea live and proliferate in extreme environments, characterized by salt concentrations up to saturation, high temperatures (although, some are cold adapted; Dassarma et al, ; Williams et al, ), high solar radiation and high ionic strength (Oren, 2013a; ; ). Under these conditions, oxygen availability is low (Oren 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…mediterranei PhaC was identified in Hrr. lacusprofundi [38]. Interestingly, this haloarchaeon is known to produce PHA at low temperatures as higher abundances of PhaC proteins were observed at low temperatures.…”
Section: Pha Synthasementioning
confidence: 98%
“…[34][35][36][37]. In 2017, it was reported that Halorubrum lacusprofundi, the third most abundant species in the Deep Lake community of Antarctica, produced PHA-like granules at low temperature [38]. To date, haloarchaeal species belonging to almost 17 genera have been reported to exhibit PHA-accumulating ability (Table 1).…”
Section: Haloarchaea As Pha Producersmentioning
confidence: 99%
See 2 more Smart Citations